1994
DOI: 10.1071/ph940517
|View full text |Cite
|
Sign up to set email alerts
|

Some Memories of the Dover Heights Field Station, 1946?1954

Abstract: The author describes the first eight years of his astronomical career. His collaboration with John Bolton, Gordon Stanley, Kevin Westfold and Dick Mc'Oee at the Dover Heights field station resulted in the detection and optical identification of the first radio sources outside the solar system. The first radio spectra, angular sizes and source variability measurements were made during this interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Some fourteen additional sources were discovered (Stanley & Slee 1950), including the now well known powerful radio galaxies Hydra A, Hercules A, Fornax A, and Pictor A. At the same time, Stanley and Slee also made more accurate measurements of the intensities of the four strongest sources with 2-Yagi antennas over the frequency range 40-160 MHz, publishing the first believable spectra, which strongly suggested that the radio emission was non-thermal (see figure 6 in Slee 1994).…”
Section: The Radiophysics Yearsmentioning
confidence: 94%
See 1 more Smart Citation
“…Some fourteen additional sources were discovered (Stanley & Slee 1950), including the now well known powerful radio galaxies Hydra A, Hercules A, Fornax A, and Pictor A. At the same time, Stanley and Slee also made more accurate measurements of the intensities of the four strongest sources with 2-Yagi antennas over the frequency range 40-160 MHz, publishing the first believable spectra, which strongly suggested that the radio emission was non-thermal (see figure 6 in Slee 1994).…”
Section: The Radiophysics Yearsmentioning
confidence: 94%
“…It was at this stage that Bolton and Stanley discussed the possibility of resuming a search for extra-solar radio sources using the sea interferometer technique, which Bolton and Slee had begun at Dover Heights with inadequate sensitivity in 1946 November (see Slee 1994). When the expedition to Brazil was cancelled, Pawsey suggested that Stanley and Bolton resume solar observations with the improved 60, 100, and 200 MHz receivers and 2-and 4-Yagi antennas, setting them up on a large concrete blockhouse at Dover Heights (see Figure 4) on the cliff edge some 79 m above the Tasman Sea and 5 km south of the entrance to Sydney Harbor.…”
Section: The Radiophysics Yearsmentioning
confidence: 99%
“…For further details on the role of the Dover Heights field station see Orchiston and Robertson (2017). For their personal reminiscences on the Dover Heights years see Bolton (1982), Slee (1994), Stanley (1994) and Westfold (1994).…”
Section: 22)mentioning
confidence: 99%
“…After serving with the Dover Heights team that elucidated the true nature of 'radio stars' (Slee, 1994), he gained further international recognition (continued) during the 1950s through the Mills-Slee-Hill catalogue of radio sources at Fleurs, and the controversy this generated vis-à-vis the Cambridge 2C survey. Bruce then went on to pioneer the detection of radio emission from various types of active stars.…”
Section: Spherical Nebulamentioning
confidence: 99%